(untitled) (Third Sector Social Economic Review, 2023)
In addition to being an important social problem, occupational accidents also cause significant economic losses for businesses. Around 4% of the total economic resources in the world are lost due to work accidents and occupational diseases. The proposed method aims to determine the risk priorities of the departments with the TOPSIS method by using the ""Risk Potential"", ""Accident Frequency Rate"", ""Accident Severity Rate"" and ""Average Cost Per Occupational Accident"" parameters. In this direction, the proposed method creates a risk map according to the period covered by the department activities in the total workflow. Since expert decisions are effective in the evaluation of the ""Risk Potential"" parameter, a fuzzy approach was preferred in order to minimize subjectivity. Other methods applied are computationally independent of expert judgments. A sample application was carried out with the proposed method and the steps of the method were tested in practice. There is no analysis method in the literature that focuses on the economic effects of occupational accidents on businesses by focusing on the occurrence of accidents and the costs that will occur after the accident. In this direction, it is thought that the proposed model will fill an important gap in the literature.